Two traditional Apulian varieties of Cucumis melo L. exhibit superior sensory and digestive profiles over common cucumber: a population-based and clinical study - Khalil, Mohamad; Renna, Massimiliano; Pietragalla, Gianni; Perniola, Valeria; Di Ciaula, Agostino; Palmitessa, Onofrio Davide; Didonna, Adriano; Santamaria, Pietro; Portincasa, Piero (Frontiers in Nutrition, 2025)
IntroductionCucumis vegetables, including the Apulian unripe melon varieties ‘Barattiere’ (BAR) and ‘Scopatizzo’ (SCO), represent important contributors to regional food agrobiodiversity.MethodsWe conducted a population-based dietary survey (N = 493), sensory evaluations, and a clinical trial to compare consumption patterns, tolerability, and physiological responses of BAR and SCO with the commonly consumed cucumber (CUC).ResultsSurvey data revealed that CUC was the most consumed (98.4%), followed by BAR (92.7%) and SCO (79.5%). However, CUC intake was most frequently linked to digestive discomfort (16.3%) and maldigestion (11.5%), whereas BAR and SCO showed better gastrointestinal tolerance. Sensory testing identified BAR as the sweetest (p < 0.00001), SCO as the crunchiest (p = 0.002), and CUC as the most bitter (p < 0.00001). In the clinical trial (15 healthy adults, randomized crossover design), ingestion of 80 g portions demonstrated that BAR and SCO elicited stronger rewarding responses in food intake control (p < 0.02), while appetite and satiety parameters remained comparable across varieties. Functional ultrasonography and breath hydrogen tests showed mild and comparable gastrointestinal effects, without significant fermentation or bothersome symptoms.DiscussionOur findings demonstrate that BAR and SCO combine greater sensory appeal with improved digestive tolerance compared to CUC. These traditional varieties may therefore be promoted as culturally relevant, palatable, and physiologically favorable alternatives to common cucumbers. Further research is warranted to assess their broader metabolic and health effects.